Fatal myopericarditis complicated with coronary vein perforation under the triple antithrombotic therapy: a case report. Issue 4 (24th April 2021) - Takasaki, Akihiro; Okamoto, Ryuji; Sugimoto, Hiroko; Dohi, Kaoru
Abstract: Background : Acute pericarditis generally follows a mild clinical course and is rarely fatal. Coronary vein involvement is rarely reported. Case summary : We report an autopsy case of cardiac tamponade from idiopathic myopericarditis due to coronary venous perforation under the triple antithrombotic therapy. A 69-year-old man was admitted to our hospital with abnormal findings on electrocardiography, bloody pericardial effusion, and mild elevation of troponin I. Oral anti-inflammatories were started and the patient followed a benign course. However, on hospital Day 5, he suddenly suffered cardiogenic shock with pulseless electric activity due to cardiac tamponade under the combination use of the dual antiplatelet drugs and an anticoagulant drug. He died despite intense medical treatment. Autopsy revealed cardiac tamponade caused by perforation in the coronary venous wall. To the best of our knowledge, this is the first description of fatal myopericarditis as a complication of coronary venous perforation. Discussion : The aetiology and mechanism remain unknown; however, we should take care for this rare complication in patients with acute myopericarditis and bloody effusion under the triple antithrombotic therapy.